Introduction and expression of the bacterial PaeR7 methylase gene in mammalian cells. - Kwoh, T J (1986)
An approach is devised for studying the role of DNA methylation in eukaryotic gene expression. The approach is based on the expression of site-specific bacterial methylase genes in animal cells. A model system using the cloned PaeR7 (an isoschizomer of Xho I) methylase gene was constructed to test the feasibility of this approach. Expression plasmids for the PaeR7 methylase gene were introduced into mouse Ltk- cells by cotransfection with the cloned chicken thymidine kinase (tk) gene. Several of the cell strains derived from Tk+ colonies were found to express the PaeR7 gene as judged by four criteria: the cellular DNA of these strains showed increased resistance to cleavage by Xho I; these strains contained cellular proteins that comigrated with pure PaeR7 methylase protein, as visualized by immunoblotting; PaeR7 methylase activity was found in vitro in crude extracts of total cellular protein from these strains; and murine adenovirus genomes grown on cells expressing PaeR7 methylase showed resistance to cleavage to PaeR7 endonuclease. The potential applications of this approach for the study of cellular and viral gene regulation, DNA repair, and restriction modification are discussed.